SEMIOTIKA PEMASARAN PADA BRAND VALUE MELALUI SIGN BERUPA LAYOUT BERITA DAN IKLAN IBADAH HAJI (Studi Komparasi pada Harian Pos Kota dengan Rakyat Merdeka) - Rustono Farady Marta; Virgitta Septyana (SEMIOTIKA: Jurnal Komunikasi, 2015)
Competing in the middle of the rush of competition between the media, the press is now incarnated as a profit-oriented industry. This can be seen through the presence of ads that support the print media, one of which is the newspaper. The newspaper is considered as one of the most effective advertising medium with all its characteristics. The pattern has now changes within marketing communication strategy, in which the news is arranged in such a manner on the same page with ads that match the topic of the news. At the level of the sign, the news is a commodity used as an advertisement, which impressed 'piggybacking' the existence of the news. Local newspaper “Pos Kota” doing it for competing with similar media in the distribution range in the scope, namely the provinces of Jakarta. The strategy is also carried out by the National Daily “Rakyat Merdeka” that have a platform and audience segment similar to “Post Kota”. Each of the newspapers have a similar strategy, but researchers trying to find differences in the construction of brand value that is reflected by the level of sign in the form of news and advertising layouts are presented with the same topic. A study marketing communication offered by Laura R. Oswald in semiotic method of marketing, where the sign, strategy, and brand value to the triangle of meanings. The approach used in this study refers to the qualitative methodology and rely on constructivist paradigm. Keywords: Oswald Marketing Secmiotics, Brand Value, Sign Layout, Pos Kota and Rakyat Merdeka